2005
DOI: 10.1007/s11120-005-2440-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Changes in Photosynthetic Activity of the Homoiochlorophyllous Desiccation-Tolerant Haberlea Rhodopensis and Desiccation-Sensitive Spinach Leaves During Desiccation and Rehydration

Abstract: The functional peculiarities and responses of the photosynthetic system in the flowering homoiochlorophyllous desiccation-tolerant (HDT) Haberlea rhodopensis and the non-desiccation-tolerant spinach were compared during desiccation and rehydration. Increasing rate of water loss clearly modifies the kinetic parameters of fluorescence induction, thermoluminescence emission, far-red induced P700 oxidation and oxygen evolution in the leaves of both species. The values of these parameters returned nearly to the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 43 publications
(26 reference statements)
6
39
0
Order By: Relevance
“…The photosynthesis was one of the latest physiological processes switched off by plant organization during dehydration, thus the chloroplast should be active and provide the energy the plant needed for protection under stress condition. Our previous investigations showed that similarly to chlorophyll content, the photochemical activity of PSII significantly decreased when leaf water content was reduced more than 70% (Georgieva et al 2005(Georgieva et al , 2007. Moreover, the integrity of thylakoids was preserved and the amount of chlorophyllprotein complexes hardly changed during desiccation (Georgieva et al 2007(Georgieva et al , 2009.…”
Section: Discussionmentioning
confidence: 95%
“…The photosynthesis was one of the latest physiological processes switched off by plant organization during dehydration, thus the chloroplast should be active and provide the energy the plant needed for protection under stress condition. Our previous investigations showed that similarly to chlorophyll content, the photochemical activity of PSII significantly decreased when leaf water content was reduced more than 70% (Georgieva et al 2005(Georgieva et al , 2007. Moreover, the integrity of thylakoids was preserved and the amount of chlorophyllprotein complexes hardly changed during desiccation (Georgieva et al 2007(Georgieva et al , 2009.…”
Section: Discussionmentioning
confidence: 95%
“…In addition a part of these centers was less susceptible to DCMU (Peeva and Maslenkova 2004). These features as well as the strong reduction of the number of active PSII centers performing S 2,3 Q B ¡ charge separation during desiccation without any changes in the energetic of the charge recombination in the rest operating centers were considered to indicate modiWcations of the redox properties of Q B (Georgieva et al 2005) related to desiccation tolerance of Haberlea. It is reasonably to suggest these modiWcations to favor S 2 Q A ¡ charge recombination under desiccation.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study was performed on detached leaves subjected to rapid desiccation in the dark (Georgieva et al 2005). The data showed a strong reduction of the total number of PSII centers in Haberlea during desiccation without any changes in the energetic of charge recombination, suggesting the involvement of a protective mechanism related to desiccation tolerance that could be speciWc for this resurrection species.…”
Section: Introductionmentioning
confidence: 90%
“…It has been shown that the peak temperature of B band increases in stress-tolerant photosynthetic organisms; for example in thermophilic cyanobacteria or desiccation-tolerant species (Govindjee et al, 1985;Sass et al, 1996;Maslenkova and Homann, 2000;Peeva and Maslenkova, 2004). It has also been shown that stresses do not affect the energetic levels of the stabilized S 2 Q B 2 charge pairs in stress-tolerant plants (Sass et al, 1996;Georgieva et al, 2005).…”
Section: Tlmentioning
confidence: 99%